(untitled) (African Journal of Biomedical Research, 2023)
Environmental pollution and work related hazard have exposed humans to various metallic agents including, mercury. The protective effect of Allium sativum (A. sativum) Linn (Garlic) on mercury-induced oxidative stress in the cerebellum of adult female Wistar rats was studied. Twenty five adult female Wistar rats weighing between 180g and 210g, used for this study were divided into five groups; Group 1 rats received distilled water and served as the control, group 2 rats were administered 3.75mg/kg body weight of Mercury (II) chloride (Hgcl2) only, group 3 rats were administered 50mg/kg body weight of A. sativum extract only, group 4 rats were administered 3.75mg/kg Hgcl2 and 50mg/kg of A. sativum extract and group 5 were administered 3.75mg/kg Hgcl2 and 100mg/kg vitamin C orally for 28 days. The body weight and neurobehavioral studies were done shortly before sacrifice on day 29. After sacrifice, the brain was dissected out and the cerebellum, processed for biochemical and histolomorphological evaluations. Data were analyzed using ANOVA at p<0.05. Results showed signs of general body weakness, decline in food and water intake, and decreased weight gain in the Hgcl2 and A. sativum + Hgcl2 groups compared with the control and other treated groups. There was reduced drop-off time in the forelimb grip strength in the Hgcl2-treated groups compared with the control. An increased lipid peroxidation, and decreased glutathione levels, SOD and GPx activities was seen in the cerebellum of Hgcl2-treated group compared with the control and other treated groups. Histomorphologically, there was reduction in the molecular layer thickness, loss of Purkinje cells and increased astrocytes population in the cerebellum of the Hgcl2-treated group compared with the control and the other treated groups. In conclusion, exposure to mercury affected muscle tone, induced oxidative stress causing morphological alterations. Aqueous extracts of Allium sativum and vitamin C decreased the rate at which mercury induced oxidative damage in the cerebellum of adult female Wistar rats